Implementasi Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam - Anis Sukmawati (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
In implementing the independent curriculum, educators are expected to be able to meet the learning needs of each student with different characteristics. Differentiation learning is the right idea to achieve the expected learning objectives. However, the facts on the ground show that it is still rare for teachers to want to do this because they do not have a clear concept for implementing it. This study aims to find out how the implementation of differentiated learning in Islamic Religious Education subjects at SMP Al Azhaar Masjid Baitul Khoir Bandung Tulungagung. This qualitative research found that in an effort to implement differentiation learning, the following steps are needed; First, planning is carried out by mapping students' initial abilities, readiness and interest in learning and finding essential material that must be learned; Second, carry out learning with content differentiation strategies, process differentiation, and product differentiation. Third, carry out an evaluation to determine the effectiveness and level of success of the objectives of the learning carried out. The researcher concluded that differentiation learning in the subject of Islamic Religious Education provides an opportunity to learn naturally, starting from the initial abilities of each student. The success of differentiation learning is also supported by good collaboration and communication between the school and student parents.